Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif melalui Olahan Pepaya dan Pisang di Pekon Sidorejo Tanggamus Lampung (Neolectura, 2020)
The community dedication-based research aims to provide insight to the community to maximize the potential of local natural resources in Pekon Sidorejo as well as enhance the economy through the creative process of Earth's produce and marketing strategies. The method is used with the method of ABCD (Asset Based Communities Development) which is a model of approach in community development. Where this approach emphasizes on the inventory of assets in the community that is considered supportive in community empowerment activities. The object of this research is the pekon Sidorejo of the district Sumberejo district of the Lampung province, which is very abundant in garden yields, especially papaya with California and bananas fruit. But on the other hand when the harvest is abundant and often not sold, papaya fruit is discarded even only used as cattle feed. The result of this dedication can provide education to the community of Sidorejo pekon, how to process papaya and bananas fruit to produce a processed product that is; Papaya Dodol, papaya pudding, candied papaya and banana chips.